A Kabbalist in Montreal: the life and times of Rabbi Yudel Rosenberg - Robinson, Ira (Touro University Press, 2020)
1. Introduction: Rabbi Yudel Rosenberg and the paradigms of Jewish modernity -- 2. On a spiderweb foundation: Yudel Rosenberg's life in small-town Poland (1859-1889) -- 3. A rabbi and rebbe in urban Poland (1890-1913) -- 4. Allright! it's America!: a rabbi in Toronto (1913-1918) -- 5. The rabbis are for the dollar: Rabbi Yudel Rosenberg and the kosher meat wars of Montreal (1919-1935) -- 6. Better to be in gehinnom: Yudel Rosenberg's halakhic voice -- 7. A folk author: Yudel Rosenberg as storyteller -- 8. Almost alone: Yudel Rosenberg as preacher -- 9. Magic, science, and healing -- 10. Those who understand Kabbala are extremely rare in OIr Generation: Rabbi Yudel Rosenberg as Kabbalist -- 11. What Is Rabbi Yudel Rosenberg's legacy? -- A chronological bibliography of the writings of Rabbi Yehuda Yudel Rosenberg.